2020
DOI: 10.1002/ps.6122
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol ability and action mechanism of dihydromaltophilin against Colletotrichum fructicola causing anthracnose of pear fruit

Abstract: BACKGROUND Anthracnose caused by Colletotrichum fructicola is one of the most important diseases in pear fruit, resulting in huge economic losses. Public awareness of protecting the environment and food safety, together with pathogen resistance to many key fungicides have led to an urgent need to develop alternative strategies for controlling fruit diseases. Here, the antifungal activity of a natural product, dihydromaltophilin [heat‐stable antifungal factor (HSAF)], against C. fructicola in vitro and in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Microscopic examination showed that the morphology of mycelium is significantly shortened, twisted and hyper-branched under HSAF treatment ( Figure 1 E). As reported for other crop and clinical fungal pathogens [ 16 , 17 , 18 ], these data suggested that a certain amount of HSAF could inhibit the germination and polarized growth of N. crassa, enabling it to be a reasonable model to investigate the antifungal mechanism of HSAF.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Microscopic examination showed that the morphology of mycelium is significantly shortened, twisted and hyper-branched under HSAF treatment ( Figure 1 E). As reported for other crop and clinical fungal pathogens [ 16 , 17 , 18 ], these data suggested that a certain amount of HSAF could inhibit the germination and polarized growth of N. crassa, enabling it to be a reasonable model to investigate the antifungal mechanism of HSAF.…”
Section: Resultssupporting
confidence: 71%
“…In C. fructicola , HSAF disrupts the coordination between cytokinesis and nuclear division, induces the production of reactive oxygen species in conidia and destroys the integrity of the conidial cell wall. HSAF specifically targets biological processes required for the formation and elongation of the germ tube but does not affect nuclear division [ 17 ]. In A. alternata , transcriptomics analysis demonstrates that HSAF disrupts the metabolic network, including the adenosine 5′-monophosphate (AMP)-activated protein kinase (AMPK) signaling pathway, sphingolipid metabolism, carbon metabolism, TCA (tricarboxylic acid) cycle, cell cycle, etc., and ultimately leads to apoptosis [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The polycyclic tetramic acid macrolactams have shown specific suppressive activity against plant pathogenic fungi and oomycetes. Alteramide B, isolated from L. enzymogenes, was shown to inhibit various plant pathogenic fungi and oomycetes in vitro [ 52 ], while the application of dihydromaltophilin (HSAF) successfully controlled Fusarium head blight in wheat [ 53 ] and post-harvest application of HSAF in pears reduced anthracnose symptoms caused by Colletotrichum fructicola [ 54 ]. Since heat-treated AZ78 extracts showed prophylactic activity against Pl.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated C. fructicola as the causal organism causing anthracnose of fruit, vegetables, and economic crops, including chili [23], pear [24], apple [25], strawberry [26], dragon fruit [27], and tea [28]. Numerous studies have pointed out various ways to control anthracnose caused by Colletotrichum spp., including, but not limited to, the application of biorational pesticides, such as essential oil [29], biocontrol strategies [30], synthetic fungicides, and heat treatments [31].…”
Section: Discussionmentioning
confidence: 99%